KORELASI ANTARA 20 METER MULTI-STAGE RUNNING TEST DAN CARDIOPULMONARY EXERCISE TESTING UNTUK MEMPREDIKSI VO2 MAX PADA ANAK LAKI-LAKI USIA 11-12 TAHUN - Arfi Fachrul Imaduddin; Yuni Susanti Pratiwi; Sunaryo B. Sastradimaja (PAIFORI, 2019)
VO2 max can be measured with two protocols, namely direct and indirect. Direct protocols are known to be valid, but more difficult and expensive. The indirect protocol is often asked of its validity, but it is practical and cheapest to use in the field. One of the indirect protocols that can be used in children is 20-meter Multi-Stage Running (20-MST). This study aimed to determine the correlation between the 20-MST with Cardiopulmonary Exercise Testing (CPET) in boys. This research used descriptive analytic study design. The subjects were 38 boys aged from 11 to 12 of extracurricular sports club members. The research variables are VO2 max results with 2 methods of measurement which are 20-MST and CPET. The statistical data were analyzed with Pearson correlation. The result of VO2 max (ml.kg-1-1.min) measurement by the method of 20-MST (28.6 ± 7.962) and result by the method of CPET (40.683 ± 10.7 31) and the correlation value between 20-MST and CPET with R=0.674. We concluded that there is a strong correlation between 20-MST test and CPET test for predicting VO2 max among boys.